Progressive cephalohematoma in a neonate revealing severe hemophilia a owing to intron 22 inversion: a case report - Peng, Cheng; Kou, Qiuyue; Xia, Qianqian; Cao, Zhongfen; Liu, Lili; Hou, Xinlin; Tang, Zezhong (Frontiers in Pediatrics, 2025)
BackgroundHemophilia A is a rare X-linked recessive bleeding disorder characterized by coagulation factor VIII (FVIII) deficiency or dysfunction. While most cases present during early childhood with joint or soft tissue bleeding, neonatal-onset hemophilia A is uncommon and often difficult to diagnose owing to its nonspecific symptoms. Early recognition and a multidisciplinary management approach are critical for preventing life-threatening complications.Case PresentationWe report a case of a male neonate admitted on day 8 of life with progressive jaundice. Physical examination revealed a large cephalohematoma and multiple skin ecchymomas. Laboratory evaluation revealed anemia and a markedly prolonged activated partial thromboplastin time (APTT). APTT mixing studies indicated factor deficiency, and factor VIII activity was <1%, confirming severe hemophilia A. Genetic analysis identified an intron 22 inversion in the F8 gene. Initial treatment included fresh frozen plasma, plasma-derived and recombinant factor VIII replacement, and phototherapy. After stabilization, the patient was transitioned to prophylactic emicizumab, which was well tolerated. At 6 weeks of age, the hematoma had nearly resolved with no further bleeding episodes observed.ConclusionEarly-onset hemophilia A in neonates may present with subtle or atypical symptoms, requiring a high index of suspicion and comprehensive diagnostic evaluation. This case underscores the value of combining functional coagulation assays and molecular testing to confirm diagnosis. It also highlights the potential benefits of early initiation of non-factor prophylaxis. Collaborative cross-disciplinary care is essential to achieve optimal outcomes in neonatal patients with bleeding disorders.